Spuriously aggressive features of a lactating adenoma prompting repeated biopsies - Janet Szabo, MD; Dairon Garcia, MD; Natalie Ciomek, MD; Laurie Margolies, MD (Radiology Case Reports, 2017)
We present an atypical presentation of a common pregnancy-related breast mass, a lactating adenoma with imaging and pathologic correlation. The patient presented with a rapidly enlarging left breast mass associated with skin changes and severe pain in the perinatal period. Core biopsies were considered discordant, and the patient went on to surgical excision for the definitive diagnosis of an infarcted lactating adenoma. The symptoms of infarction may obscure the diagnosis of common entities and result in additional evaluation.